541 The analyse of the antioxidant effect of natural peloidotherapy in aging process (Balneo and PRM Research Journal, 2024)
Abstract: Medical research has developed remarkably in recent years, including theinvolvement of the glutathione peroxidase (GPx) family of enzymes in the course ofhuman aging, with numerous clinical studies published in the literature reporting thisparticularfact. Thus, mud therapy and its effect on biological aging have been representedin papers that have been published to date. Papers published in the literature analyzingGPx vari‐ation during sapropelic mud therapy suggest the beneficial effect of this familyof en‐zymes in diseases with an important inflammatory component, mainly monitoredin patients with osteoarthritis. This study investigated the effects of sapropelic mud treat‐ment on GPx values in patients receiving treatment with sapropelic mud at the Balnealand Rehabilitation Sanatorium of Techirghiol, Romania. We included 52 patients, splitinto two groups, who received treatment with cold mud baths and warm mud baths.Values close to statistical significance were found in patients who received treatment withcold mud baths in terms of mean GPx values at the four‐time points studied. Fur‐therstudies evaluating GPx in patients receiving sapropelic mud treatment are needed.Keywords: glutathione peroxidase (GPx), sapropelic mud, peloidotherapy, balneotherapy